Incidence of Low Seroimmunity to Hepatitis B Virus in Children With Inflammatory Bowel Disease. Issue 5 (November 2017) - Watts, Abhishek; Bennett, William E.; Molleston, Jean P.; Gupta, Sandeep K.; Croffie, Joseph M.; Waseem, Shamaila; McFerron, Brian A.; Steiner, Steven J.; Kumar, Sanjay; Vanderpool, Charles P.; Hon, Emily C.; Bozic, Molly A.; et al.
ABSTRACT: Objectives: Patients with inflammatory bowel disease (IBD) often receive immunosuppressive therapy, which may make them vulnerable to infections such as hepatitis B. We hypothesized that hepatitis B virus titers are low in the vaccinated pediatric population with IBD. The aims of our study were to identify the incidence of lower titers of hepatitis B surface antibody (HBsAb) and determine which patient factors may be associated with lower HBsAb titers. Methods: Patients with diagnosis of IBD, ages 5 to 18 years, were prospectively enrolled. Patients were confirmed to have had a full series of hepatitis B vaccination. Quantitative serum HBsAb titers were measured and logistic regression analysis with independent variables of age, sex, race, disease phenotype, surgery, medications and a dependent variable of adequate HBsAb titers (> 10 mIU/mL) was performed. Results: Of the 116 patients enrolled, 57 were boys and 59 were girls. 75 patients had a diagnosis of Crohn disease; 32 had a diagnosis of ulcerative colitis; and 9 patients had been diagnosed as having indeterminate colitis. At the time of the study, 15 patients were taking corticosteroid, 66 on an immunomodulator, and 53 on a biologic. Sixty percent of patients in the 5- to 10-year age group had protective titers versus 22% to 27% in the older groups, P  = 0.04. Only 28% of the 116 patients had HBsAb titers of >10m IU/mL. Twenty percent of the patients taking corticosteroids, 27% taking immunomodulators, and 24% taking biologics were found to be seroimmune. Conclusions: Nearly two-thirds of pediatric patients with IBD have low titers against hepatitis B virus. Titers were highest in the younger patients. No patient-specific variable, such as the use of immunosuppressants, appeared to influence these low titers.